The Impact of China’s Slowdown on the Asia Pacific Region : An Application of the GVAR Model - Inoue, Tomoo; Kaya, Demet; Ohshige, Hitoshi (World Bank, Washington, DC, 2015)
An export-oriented development strategy fostered the Asia Paciﬁc region’s economic success, making it the fastest growing region in the world. In recent years, despite waning demand from the crisis-hit Western economies, the accelerating demand from China boosted intraregional trade in Asia. Although China’s Asian trading partners beneﬁt from increasing exports to China, this stronger linkage with China has made them more vulnerable to the risk of a Chinese slowdown. This paper examines the impact of a negative Chinese gross domestic product (GDP) shock on Asian economies by employing the Global Vector Autoregressive (GVAR) model, using the dataset through the third quarter of 2014 for 33 countries. The analysis finds that a negative Chinese GDP shock impacts commodity exporters, such as Indonesia, to the greatest extent, reﬂecting both demand and terms of trade shocks. Export-dependent countries in the East Asian production cycle, such as Japan, Malaysia, Singapore and Thailand, are also severely aﬀected. The analysis also finds that a negative shock to China’s real GDP would not only have an adverse eﬀect on the price of crude oil, as some previous studies have also shown, but also on the prices of metals and agricultural products. The study also investigates the impact of a potential negative shock to the real GDP of the United States on Asian countries, and determines that although the U.S. economy has a larger inﬂuence on Asian economies than China’s economy, the Asian countries are more exposed to China than ever through increased economic ties.